Gender Differences in Selection of Permanent Pacemaker Implantation at Manmohan Cardiothoracic Vascular and Transplant Centre, Kathmandu, Nepal - Khanal, Jeevan; Poudyal, Ratna Raj; Devkota, Surya; Thapa, Sanjeev; Shrestha, Amit (Journal of Nobel Medical College, 2015)
Background: Permanent pacemaker implantation is a minimally invasive surgical procedure in the management of patients with cardiac rhythm disturbances. Previous studies have reported gender differences in pacemaker selection. There is lack of evidences in selection of pacemaker mode with respect to gender in Nepal. Therefore, this study was performed to compare the frequency of implantation between men and women.Objectives: This study was performed to compare the frequency of implantation rate between men and women.Methods: The present study is based on all consecutive pacemaker implantations in a single centre between April 2014 and May 2015. A total of 116 patients were categorized into two cohorts according to the type of pacemaker implanted- single chamber or dual chamber. Data were presented as means ± standard deviation (SD) for continuous variables and as proportions for categorical variables. Comparison of continuous variables between the groups was made with independent Student’s t-test. For discrete variables distribution between groups were compared with Chi-square test.Results: The mean age (±SD) of total population at implant was 64.08 (± 15.09) years. Dual chamber units were implanted in 44 (37.93%) of patients, single chamber in 72 (62.06%). Only 14 women (31.81%) received dual chamber compared with 42 women (58.33%) who received single chamber (Chi-square=18, DF=1, P = 0.0084). Complete atrioventricular block was the commonest (56.03%) indication for permanent pacemaker insertion followed by sick sinus syndrome (33.62%), symptomatic high-grade AV block (11.20%). Hypertension (dual chamber 21.55%, single chamber 40.51%) was the most common comorbidity in both cohorts.Conclusions: Women were more likely to receive single chamber systems and less likely to receive dual chamber systems than men. Journal of Nobel College of Medicine Vol.4(1) 2015: 15-20